(5x(2)-7)=(2x(2)+3x+4)

Simple and best practice solution for (5x(2)-7)=(2x(2)+3x+4) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (5x(2)-7)=(2x(2)+3x+4) equation:



(5x(2)-7)=(2x(2)+3x+4)
We move all terms to the left:
(5x(2)-7)-((2x(2)+3x+4))=0
We add all the numbers together, and all the variables
(+5x^2-7)-((+2x^2+3x+4))=0
We get rid of parentheses
5x^2-((+2x^2+3x+4))-7=0
We calculate terms in parentheses: -((+2x^2+3x+4)), so:
(+2x^2+3x+4)
We get rid of parentheses
2x^2+3x+4
Back to the equation:
-(2x^2+3x+4)
We get rid of parentheses
5x^2-2x^2-3x-4-7=0
We add all the numbers together, and all the variables
3x^2-3x-11=0
a = 3; b = -3; c = -11;
Δ = b2-4ac
Δ = -32-4·3·(-11)
Δ = 141
The delta value is higher than zero, so the equation has two solutions
We use following formulas to calculate our solutions:
$x_{1}=\frac{-b-\sqrt{\Delta}}{2a}$
$x_{2}=\frac{-b+\sqrt{\Delta}}{2a}$

$x_{1}=\frac{-b-\sqrt{\Delta}}{2a}=\frac{-(-3)-\sqrt{141}}{2*3}=\frac{3-\sqrt{141}}{6} $
$x_{2}=\frac{-b+\sqrt{\Delta}}{2a}=\frac{-(-3)+\sqrt{141}}{2*3}=\frac{3+\sqrt{141}}{6} $

See similar equations:

| c+-83=10 | | p+20=-4p-20 | | 7w+25=3(w+7) | | f-99=-83 | | 3/2v+3=2/3v+4/3 | | 74+17x=142 | | p-29=60 | | 9x+7=-6+5x+25 | | 6x-13=4x=11 | | (g-2)/2=7/2 | | 10q-2q+4=12 | | 3n+83n-8=0 | | 3x+15=2x+10+x | | -15=3x-5 | | -13+2x=5 | | 4(v+2)=7v-19 | | 5x+3x-1=7 | | 2(2x+3)=-6(+9) | | 6-9t=15(t+2) | | 2(−4x+2)+5x−2=-19 | | 22=-8b-3b | | 14x+3+157=4x10 | | x-(.05)(X)=200000 | | -5x–3=12 | | 3x+2=5x−8 | | -96=-4p | | 9x+7=-6+25 | | -5u+2(u+2)=7 | | t-13=76 | | -0.25(x-3)=10 | | -v+60=226 | | 4(x+3)=4=8(1/2x+1) |

Equations solver categories